2012
DOI: 10.1016/j.powtec.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Liquids' atomization with two different nozzles: Modeling of the effects of some processing and formulation conditions by dimensional analysis

Abstract: Liquid atomization is a largely widespread unit operation. The disintegration of a liquid into droplets depends on the nature of the nozzle, on the process parameters as well as physicochemical characteristics of the fluid. The aim of this work is to study the contribution of the process (liquid outlet speed and air pressure) and physicochemical (viscosity and surface tension) factors on the size distribution of droplets generated by single- and two-fluid flat spray nozzles. The obtained droplet median diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
6
51
0
Order By: Relevance
“…Several literature studies confirmed this trend (Chigier, 1976;Nguyen and Rhodes, 1998;Nukiyama and Tanasawa, 1939;Lefebvre, 1980); furthermore, it was pointed out that air pressure is a crucial process parameter in the atomisation operation (Chigier, 1976;Ehlers et al, 2010;Hede et al, 2008a;Juslin et al, 1995;Lefebvre, 1980;Mandato et al, 2012;Nguyen and Rhodes, 1998).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Several literature studies confirmed this trend (Chigier, 1976;Nguyen and Rhodes, 1998;Nukiyama and Tanasawa, 1939;Lefebvre, 1980); furthermore, it was pointed out that air pressure is a crucial process parameter in the atomisation operation (Chigier, 1976;Ehlers et al, 2010;Hede et al, 2008a;Juslin et al, 1995;Lefebvre, 1980;Mandato et al, 2012;Nguyen and Rhodes, 1998).…”
Section: Introductionmentioning
confidence: 78%
“…These processes involve the formation of liquid binder droplets by atomisation, which is a critical step, as it directly influences the wetting of fine powder particles and their ability to adhere one to each other and form agglomerates (Iveson et al, 2001;Litster and Ennis, 2004;Mandato et al, 2012;Saad, 2011). Besides, it has been evidenced that the droplet size produced by atomisation is highly correlated to the sizes of final particles in spray-drying and wet agglomeration processes (Cuq et al, 2013;Hede et al, 2008a;Iveson et al, 2001;JimenezMunguia, 2007;Leuenberger et al, 2006;Marmottant, 2001;Parikh, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations